2013
DOI: 10.1186/1475-2891-12-39
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating 25-hydroxyvitamin D according to vitamin D binding protein genotypes after vitamin D3 or D2supplementation

Abstract: BackgroundIt is not known whether genetic variation in the vitamin D binding protein (DBP) influences 25-hydroxyvitamin D levels [25(OH)D] after vitamin D supplementation. We aimed to investigate the changes of total 25(OH)D, 25(OH)D3 and 25(OH)D2 in a Thai cohort, according to type of vitamin D supplement (vitamin D3 or D2) and DBP genotype, after receiving vitamin D3 or D2 for 3 months.MethodsThirty-nine healthy subjects completed the study. All subjects received 400 IU of either vitamin D3 or D2, plus a cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 21 publications
9
76
3
Order By: Relevance
“…Single nucleotide polymorphisms (SNPs) involved in the synthesis (DHCR7 and CYP2R1), binding and transportation (DBP/GC) and degradation (CYP24A1) of vitamin D and its metabolites have been shown to contribute to differences in the vitamin D response to supplementation [15,[24][25][26]. In contrast to findings from other studies [12], the change in 25(OH)D3 concentrations after therapy in our study was not dependent on the age and BMI of the study participants at baseline.…”
Section: Discussioncontrasting
confidence: 91%
“…Single nucleotide polymorphisms (SNPs) involved in the synthesis (DHCR7 and CYP2R1), binding and transportation (DBP/GC) and degradation (CYP24A1) of vitamin D and its metabolites have been shown to contribute to differences in the vitamin D response to supplementation [15,[24][25][26]. In contrast to findings from other studies [12], the change in 25(OH)D3 concentrations after therapy in our study was not dependent on the age and BMI of the study participants at baseline.…”
Section: Discussioncontrasting
confidence: 91%
“…In addition, we found that women had significantly higher se vitD than men. This study supports that vitD supplementation increases se vitD (24,30,31). Sixty-two percent of participants took vitD supplementation.…”
Section: Discussionsupporting
confidence: 82%
“…Nimitphong et al reported a lesser increase in serum 25-OHD after 3 months of 400 IU/day vitamin D3 supplementation in individuals with the GC(rs4588) CA or AA alleles when compared to CC homozygous individuals. However, no such difference was found when the supplement was vitamin D2 [130]. The group also found a significant association between variants in the PTH gene promoter and serum 25-OHD concentrations.…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 84%